N2 disease in non-small-cell lung cancer: straight to surgery?. (March 2018) - Sanchez-Lorente, David; Guzman, Rudith; Boada, Marc; Guirao, Angela; Carriel, Nicole; Molins, Laureano
The correct treatment for patients with non-small-cell lung cancer and ipsilateral mediastinal involvement (N2) remains a challenge. The heterogeneity of this group of patients has been shown, as well as many different prognostic factors, that will determine a specific management to each of them. Although the standard treatment is based on a multimodality therapy consisting of chemotherapy, radiotherapy and surgery, surgery is not always indicated. The selection of patients who are going to be operated, reminds being a key point of the treatment of this disease. Recent reports on operable N2 disease have been reviewed by our group in order to discuss surgery indications and when to bring it about, with the possibility to go straight to surgery.